Sosialisasi Pembelajaran dengan Pendekatan Etnopedagogi pada Guru-Guru di Kecamatan Pujut Lombok Tengah - Yayuk Andayani; Yunita Arian Sani Anwar; Lalu Rudiyat Telly Savalas (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Ethnopedagogy can be an effective tool for connecting science and culture through learning with an ethnopedagogy approach. However, from the results of observations and interviews with teachers and students at SMAN 1 Pujut Central Lombok, learning with an ethnopedagogy approach is not yet known even though in the area there are many cultural varieties that have the potential to be a source of learning chemistry or science. The main problem is in the limited knowledge and experience of teachers so it is necessary to carry out socialization activities. This socialization activity was attended by 30 Chemistry and Science teachers from 9 schools in Pujut district, Central Lombok. The success of socialization activities is measured by the response of teachers using questionnaires for 4 (four) indicators, namely: 1) ethnopedagogy knowledge, 2) knowledge of learning with ethnopedagogy, 3) the ability to connect ethnopedagogy in learning, and 4) the application of learning with ethnopedagogy. Based on the results of the teacher's response analysis, it is known that the teacher's knowledge of ethnopedagogy is getting better (83.3%), the teacher's understanding of learning with an ethnopedagogy approach is also getting better (83.3%), the ability to connect ethnopedagogy with learning is very good (66.7%), and the experience of applying learning with an ethnopedagogy approach is getting easier (83.3%). Thus, it can be concluded that socialization activities for teachers in Pujut Sub-district of Central Lombok have been carried out well and can increase teachers' knowledge and understanding of learning with an ethnopedagogi approach. It is hoped that schools can facilitate teachers to be able to increase their knowledge so that they are able to apply learning that integrates the surrounding culture in their respective schools so that learning is more meaningful and fosters an attitude of cultural care for students.